2019
DOI: 10.4102/sajcd.v66i1.568
|View full text |Cite
|
Sign up to set email alerts
|

The effects of combined exposure of solvents and noise on auditory function – A systematic review and meta-analysis

Abstract: Background Chemical substances can negatively affect the auditory system. Chemical substances alone or combined with high-level noise have recently become a major concern as a cause of occupational hearing loss. Objective To assess the combined effect of solvents and noise versus solvents only, or noise only, on the auditory function of workers. Method Published articles which included noise and/or solvent exposure or combined effects of solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…Another research found that around 86.2% of workers experience acute respiratory problems due to exposure to toluene at work (Nakhooda et al 2019). The research showed that the average exposure to non-carcinogenic toluene was 1.67, which is above the threshold.…”
Section: Discussionmentioning
confidence: 95%
“…Another research found that around 86.2% of workers experience acute respiratory problems due to exposure to toluene at work (Nakhooda et al 2019). The research showed that the average exposure to non-carcinogenic toluene was 1.67, which is above the threshold.…”
Section: Discussionmentioning
confidence: 95%
“…This is due to the ill-effect of ototoxic chemicals (often divided into workplace chemicals and medications) which are proved to have a synergic effect on our hearing system. Solvents damage the neurological pathways as well as the cochlea resulting in an irreversible hearing loss which is more prominent if there happens to be an exposure to a combination of noise and solvents [8]. More than 700 chemicals are regarded to be ototoxic in nature and this fact is often neglected in case of cochleotoxic non-steroidal anti-inflammatory drugs which often cause sensorineural hearing loss [9].…”
Section: Occupational Exposurementioning
confidence: 99%
“…Johnson and Morata (2010) reported impact on cochlear and central auditory processing structures owing to ototoxic properties from several solvents, for example, styrene, toluene, xylene, ethylbenzene, trichloroethylene, n-hexane, jet fuel, white spirit and other solvent mixtures. Worker-based research studies have focussed mainly on styrene, toluene, lead, mercury, carbon disulphide and carbon monoxide (Johnson & Morata, 2010;Nakhooda, Sartorius, & Govender, 2019). Table 1 shows a review of chemicals (and workplaces) that are potentially ototoxic.…”
Section: Chemicals With or Without Noise Poison Peoples' Earsmentioning
confidence: 99%
“…In summary, exposure to chemicals in the workplace may be ototoxic. If combined exposures to chemicals and noise occur, then the risk for hearing loss is exacerbated, for example, noise and multiple solvent exposures (Nakhooda et al, 2019) or TB medications use/exposure (Khoza-Shangase, 2018).However, while this is a known global concern, in South Africa, exposure to chemicals in the workplace is barely/hardly documented.…”
Section: Chemicals With or Without Noise Poison Peoples' Earsmentioning
confidence: 99%